Analisis Pengendalian Kualitas Produk Telur Asin menggunakan Peta Kontrol P-Chart di UMKM HTM Jaya Brebes - Ashar, Nurcahya Yulian; Rosyadi, Humam; Nabilah, Zizka Syaikhahtun (Mandalika Mathematics and Educations Journal, 2025)
This study aims to analyze product quality control using the P-chart control chart method at UMKM HTM Jaya Brebes, a small business that produces salted eggs in Brebes, Central Java. A total of 20,582 eggs were observed during the production process in July 2024, with a total of 1,039 defective units. The study uses Statistical Quality Control (SQC) tools such as control limits (UCL and LCL) and quality cost analysis. The P-chart was used to monitor and evaluate the proportion of defective products, identifying several points outside the control limits, indicating a lack of process stability. Additionally, fishbone diagrams were used to analyze root causes of defects such as shell damage and freshness issues. The analysis also included quality cost optimization, showing the importance of balancing quality assurance and control costs to improve product efficiency. The findings emphasize that P-chart implementation can help small industries enhance product quality and maintain consumer satisfaction.